The semi-synthetic flavonoid 2′, 3′, 4′-trihydroxyflavone (2-D08) inhibits both SN-38- and cytokine-evoked increases in epithelial barrier permeability in an in vitro intestinal mucositis model. Issue 21 (7th October 2022) - Marsh, Dylan T.; Smid, Scott D.
Abstract : The novel flavonoid 2′, 3′, 4′-trihydroxyflavone (2-D08) reduces ROS generation and inhibits both SN-38- and cytokine-evoked increases in epithelial permeability in vitro . Abstract : The chemotherapeutic drug irinotecan and its active metabolite SN-38 have been linked to the development of off-target gastrointestinal toxicity and inflammation, termed gastrointestinal mucositis (GIM). Flavonoids possess antioxidant and anti-inflammatory effects in models of gastrointestinal inflammation; however, few studies have investigated their potential in ameliorating chemotherapy-induced GIM. Here, we characterised the intestinal epithelial barrier-protective and antioxidant capacity of the novel flavonoids 2′, 3′, 4′-trihydroxyflavone (2-D08) and transilitin in comparison with flavones myricetin and quercetin in vitro via viability and permeability assessments in Caco-2 epithelial monolayers exposed to 7-ethyl-10-hydroxycamptothecin (SN-38). Transilitin, 2-D08 and myricetin maintained barrier function in the presence of SN-38, with 2-D08 proving most effective. 2-D08 was the most effective inhibitor of cytokine-evoked increases in epithelial permeability, with myricetin providing modest protection; quercetin afforded no significant protection against either SN-38 or cytokine-evoked reductions in barrier integrity. Each flavonoid significantly reduced tert -butyl hydroperoxide ( t bhp)-induced reactive oxygen species (ROS) generation, although 2-D08 was comparatively less effective. These results highlight a novel role for 2-D08 as an inhibitor of both SN-38 and cytokine-evoked increases in epithelial permeability, with lesser barrier protective roles ascribed to transilitin and myricetin and not correlated with antioxidant capacity. Such novel flavonoids as 2-D08 may have active or adjunctive roles in ameliorating chemotherapy and inflammation-evoked changes in intestinal barrier function.